Materiality, mythology & tactical traces: a study of the Johannesburg Art Gallery and Joubert Park's trajectory through creative research - McClure, Matthew Denham Hugh (My University, 2021)
The Johannesburg Art Gallery (JAG) and Joubert Park are spaces that have accumulated and attracted various forms of mythologies and tangible and intangible traces throughout the course of their long histories. Both the gallery and the park are situated in a complex and multi-layered social, economic, historical and cultural environment in Johannesburg, and were founded on colonial principles of cultural programming by the dominant British society at the time of their establishment in what was then a new city, upon which powerful groups and individuals were stamping their authority. Through the process of research and an accompanying creative component, I identify six different traces (The Darling Postcard, The Old Fence, The Play by Taub, The Exhibition by Hobbs, The Panel Discussion and The Lutyens Plans) connected in various ways to both Joubert Park and the JAG. I aim to show how each of these traces can be viewed as registers of many different impositions, interrogations and interactions of these spaces by different groups and individuals throughout their histories. I map out how these traces interrogate, maintain or destabilise the “mythologies of place”, as Anita Bakshi has called them, that are inscribed into the fabric of both the park and the gallery, acting, in certain cases, as what Michel de Certeau would identify as “tactics” or “strategies”. I draw on an understanding of Jane Bennett’s “vital materiality”, and the ways that both tangible and intangible traces can and do influence and nuance the negotiation of a space. Through what Hazel Smith and Roger Dean have identified as practice-led research and research-led practice, as applied to the study of the six traces, I have attempted to map a trajectory of both the gallery and the park from their inceptions through to the contemporary moment I have done this in order to further interrogate the role of heritage, historical and public spaces in Johannesburg and possibly also South Africa at large. I argue that it is through this intersectional form of research that public and private efforts at urban planning, preservation and conservation can best be approached
A research report is submitted as a partial requirement for the degree of Masters History of Art, coursework and research report, Faculty of Humanities, University of the Witwatersrand, 2021